Parents' participation in school activities - Uchau, Edwin Laway (Universiti Malaysia Sarawak (UNIMAS), 2002)
This study sought to clarify parents' level of participation, the barriers they encounter when trying to participate in school activities, school efforts in enhancing parents' participation in school activities and the problems school encounter in trying to get parents' active participation in school activities .. Apart from that it also revealed the kind of activities parents mostly participated in and how the school-level variables influence the degree of parents' involvement in school activities. The information gathered through semi-structured interviews and questionnaires ofparents' activities revealed that parents' involvement was influenced by several factors which include parent's cliques, parent's education, attitudes ofthe school staff, cultural influences and family issues. It also showed the extent of school success in getting parents to get involve in school activities were influenced by several factors within and beyond the school capability to overcome them. The results of this study show that many forms of parents' involvement such as the environment at home are not easily influenced by school-level variables. However, several forms of parents' involvement including parents' volunteerism and participation in parentteachers organizations can be increased when teachers attempt to contact parents more effectively. At the same time the result also showed the school limitation in its effort to bring parents closer to the school. The findings have implications on both the school and parents that affect their level of participation and the extent of success on the school side. An understanding of these factors will provide ways to increase and improve parents' involvement.